Process Engineering Renewal 1: Background and Training - ric Schaer, Schaer; Jean-Claude Andr , Andr (John Wiley & Sons, Incorporated, 2020)
Process engineering emerged at the beginning of the 20th Century and has become an essential scientific discipline for the matter and energy processing industries. Its success is incontrovertible, with the exponential increase in techniques and innovations. Rapid advances in new technologies such as artificial intelligence, as well as current societal needs sustainable development, climate change, renewable energy, the environment are developments that must be taken into account in industrial renewal. Process Engineering Renewal 1 the first volume of three focuses on training, demonstrating the need for innovation in order for the field to have a framework that is sustainable, in a highly changeable world.